Studi Literatur Komparatif Karakteristik Pembelajaran Mendalam pada Kurikulum Merdeka Indonesia dan Sistem Pendidikan Finlandia - Sofia Annisa; Rizka Fadhilah Priono; Adellina Ahmad Zain Nainggolan (Scidacplus, 2026)
Deep learning is gaining increasing attention in educational transformation due to its role in developing critical thinking, problem-solving, collaboration, and 21st-century competencies. Indonesia, through its Independent Curriculum (Kurikulum Merdeka), and Finland, through its education system, both implement learning oriented toward deep understanding, but with different characteristics. This study aims to compare the characteristics of deep learning in the Indonesian Independent Curriculum and the Finnish education system. The study used the Systematic Literature Review (SLR) method by reviewing 12 articles obtained from Google Scholar, ScienceDirect, and ERIC according to established inclusion and exclusion criteria. The results show that deep learning in the Independent Curriculum is characterized by student-centered learning, meaningful learning, contextual learning, critical thinking, problem-solving, reflection, and authentic assessment. Meanwhile, the Finnish education system emphasizes phenomenon-based learning, interdisciplinary learning, collaboration, scientific reasoning, and experiential learning. Both systems share similarities in developing 21st-century competencies, but differ in their implementation approaches. The findings of this study provide implications that strengthening phenomenon-based learning and cross-disciplinary integration can be alternative strategies to strengthen the implementation of in-depth learning in the Independent Curriculum.